The Potential Role of Mir-1290 in Cancer Progression, Diagnosis, Prognosis, and Treatment: An Oncomir or Onco-Suppressor Microrna? - Echeverria-Morgado, J (John Wiley and Sons Inc, 2022)
Cancer is one of the leading causes of death in humans because of the lack of early diagnosis, distant metastases, and the resistance to adjuvant therapies, including chemotherapy and radiotherapy. In addition to playing an essential role in tumor progression and development, microRNAs (miRNAs) can be used as a robust biomarker in the early detection of cancer. MiR-1290 was discovered for the first time in human embryonic stem cells, and under typical physiological situations, plays an essential role in neuronal differentiation and neural stem cell proliferation. Its coding sequence is located at the 1p36.13 regions in the first intron of the aldehyde dehydrogenase 4 gene member A1. miR-1290 is out of control in many cancers such as breast cancer, colorectal cancer, esophageal squamous cell carcinoma, gastric cancer, lung cancer, pancreatic cancer, and plays a vital role in their development. Therefore, it is suggested that miR-1290 can be considered as a potential diagnostic and therapeutic target in many cancers. In addition to the importance of miR-1290 in the noninvasive diagnosis of various cancers, this systematic review study discussed the role of miR-1290 in altering the expression of different genes involved in cancer development and chemo-radiation resistance. Moreover, it considered the regulatory effect of natural products on miR-1290 expression and the interaction of lncRNAs by miR-1290. © 2021 Wiley Periodicals LLC